2015
DOI: 10.11621/pir.2015.0204
|View full text |Cite
|
Sign up to set email alerts
|

Styles of parent-child interactions in families with preschool-age children

Abstract: With regard to cultural-historical and activity approaches, collaborative activity with an adult, including communication as a type of meta-activity, is considered to be the necessary mechanism of child development. A child is considered to be an active partner, possessing his/her own motives, and is guided by mental representations of the parent and interactions with him/her. Russian psychologists have developed a range of parenting style classifications; however, these styles primarily emphasize a parent's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…They suggested that the dominationsubordination misbalance caused potential di culties in further development. The dominant interaction behaviors of parents' questions and commands, and children's response and compliance observed in the present study is similar to a Chinese study [23], an American study [24], and a Russian study [22]. Speci cally, in the Russian study, the most frequent type of PCI was dominant parent-subordinate child.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…They suggested that the dominationsubordination misbalance caused potential di culties in further development. The dominant interaction behaviors of parents' questions and commands, and children's response and compliance observed in the present study is similar to a Chinese study [23], an American study [24], and a Russian study [22]. Speci cally, in the Russian study, the most frequent type of PCI was dominant parent-subordinate child.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, Shvedovskaya and Archakova addressed the activity-based typology of PCI according to con ictual, harmonious, distant, and dominant (divided into "dominant parent-subordinate child" and "dominant child-indulgent parent" subgroups) types, which differ both in activity (role distribution, character of realization of task-oriented collaboration) and emotional (emotional vector of interactions, emotional reaction to success or failure) aspects of interactions [22]. They suggested that the dominationsubordination misbalance caused potential di culties in further development.…”
Section: Discussionmentioning
confidence: 99%
“…Regression test results indicate the influence of parent-child interaction on subjective well-being. According to Shvedovskaya and Archakova (2015), a child is an active partner, has his motives, and is guided by the mental representation of parents and the interaction between the two. The research of Casas et al (2008) also proved that the interaction between parents and children affects the well-being of one's life.…”
Section: Discussionmentioning
confidence: 99%
“…подросток в семейном взаимодействии выступает активным субъектом отношений и руководствуется своими представлениями о родителях, идеальными и реальными образами взаимодействия с ними и применения ими воспитательных воздействий, что может не совпадать с оценкой данных аспектов родителями. на необходимость подобного «перекрестного» оценивания стиля воспитания в семье с позиции обеих сторон указывается в работах российских и зарубежных исследователей (Shvedovskaya & archakova, 2015;Gracia et al, 2005).…”
Section: дискуссионные вопросыunclassified